2019
DOI: 10.1146/annurev-orgpsych-012218-015009
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Performance Management: Searching for Value

Abstract: This article reviews the history of performance management (PM), beginning with performance evaluation. We discuss various strategies that have been used to enable accurate ratings as well as cognitive processes and contextual factors that have been shown to significantly impact ratings. We raise questions about the concept of true performance and whether raters can be enabled and motivated to make accurate ratings. We progress to discussing more structured and comprehensive PM processes that typically involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 61 publications
1
55
0
Order By: Relevance
“…For many years human resources leaders have been working on visualizing more efficient and effective ways to manage performance. Although I-O practitioners may differ on the nuances, there is today a strong consensus on what good practice looks like: Simpler administration; regular, supportive, helpful, motivating performance conversations all year long; evaluations that don't rest solely on the retrospective view over an entire year's performance of the manager alone; greater clarity for employees on expectations and greater corresponding commitment from employees to exceed those expectations (Aguinis, 2019;Pulakos et al 2019).…”
Section: Final Thoughtsmentioning
confidence: 99%
See 1 more Smart Citation
“…For many years human resources leaders have been working on visualizing more efficient and effective ways to manage performance. Although I-O practitioners may differ on the nuances, there is today a strong consensus on what good practice looks like: Simpler administration; regular, supportive, helpful, motivating performance conversations all year long; evaluations that don't rest solely on the retrospective view over an entire year's performance of the manager alone; greater clarity for employees on expectations and greater corresponding commitment from employees to exceed those expectations (Aguinis, 2019;Pulakos et al 2019).…”
Section: Final Thoughtsmentioning
confidence: 99%
“…There has recently been a groundswell of dissatisfaction with performance management (e.g., Buckingham & Goodall, 2019). In the very first volume of this journal, Murphy (2008) documented and bemoaned the lack of progress in improving performance management design and execution.Coming out of his and other critiques (Pulakos et al, 2019), various sound ideas have emerged for improving performance management processes. These include radical simplification (Efron & Ort, 2010); incorporating more of a future-rather than past-focus (Buckingham & Goodall, 2015); abandoning forced distributions (Ledford et al, 2016); improving relevant manager training and strengthening managerial accountability for effective performance management (e.g., Mone & London, 2010); collecting performance feedback from multiple sources (Campion et al, 2019); and, perhaps most importantly, stressing ongoing performance conversations as a -perhaps the key-element in managing performance (Pulakos et al, 2015; see Pulakos et al, 2019;Aguinis, 2019, for comprehensive scholarly and popular treatments, respectively).…”
mentioning
confidence: 99%
“…also Shore and Wright 2000). In their review on the evolution of performance management, Pulakos et al (2019) come to the conclusion that "formal performance management processes disengage employees, cost millions, and have no impact on performance". In the context of taxpayer honesty, Kucher and Götte (1998) have shown that observing tax laws and regulations is not just a matter of how strictly taxpayers are controlled.…”
Section: Quantitative Metrics As Proxy Indicatorsmentioning
confidence: 99%
“…However, managing performance at micro level, particularly at public employee and organization level, is a least explored arena in public-sector research (Dooren et al, 2015;Pulakos et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have demonstrated that improvements in the measurement system will lead to improvements in the performance of a public-sector organization, the results are still mixed (Arnaboldi et al, 2015). The literature mostly discusses performance measurement issues, challenges, indicators, content, or performance management in terms of performance information, goal clarity, and budgeting (e.g., Gao, 2015;Kroll, 2015;Mauro et al, 2016;Pandey, 2015;Pulakos et al, 2019).…”
Section: Introductionmentioning
confidence: 99%